The impact of minimum wages on informal and formal labor market outcomes: Evidence from Indonesia - Maike Hohberg; Jann Lay (IZA Journal of Labor & Development, 2015)
This paper studies the effects of minimum wages on informal and formal sector wages and employment in Indonesia between 1997 and 2007. Applying fixed-effects methods, the estimates suggest that minimum wages have a significant positive effect on formal sector wages, while there are no spillover effects on informal workers. Regarding employment, we find no statistically significant negative effects of minimum wages on the probability of being formally employed. These findings suggest that employers use adjustment channels other than employment or that effects such as a demand stimulus on a local level outweigh the possible negative employment effects.
Keywords: J08; J46; 330; Minimum wages; Employment effects; Informal sector; Wage spillover effects